Forecasting Farmer Exchange Rates as a Welfare Proxy: BetaSutte's Role in Predicting Agricultural Income Stability in Indonesia - Ansari Saleh Ahmar (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study presents BetaSutte — a novel hybrid forecasting model applying the four-lag ?-Sutte Indicator to OLS-detrended residuals rather than to the raw level series — and evaluates it on Indonesia’s monthly Nilai Tukar Petani (NTP, Farmer Exchange Rate), a composite agricultural welfare index for over 40 million farming households. Using 84 monthly observations from January 2019 to December 2025 (Badan Pusat Statistik), the model separates NTP into a linear trend component and a residual , applies the ?-Sutte formula to the stationary residual domain, and generates forecasts as with ? optimised by grid search. Calibrating on the first 60 observations (January 2019–December 2023), the OLS trend explains 82.75% of NTP variance , and the optimal ? = 0.30 yields in-sample RMSE = 1.6887, MAE = 1.3695, and MAPE = 1.2881% — an 11.5% RMSE reduction versus the trend-only baseline. Crucially, two full years of genuinely out-of-sample validation (January 2024–December 2025, n = 24) confirm BetaSutte’s operational superiority: RMSE = 5.4841 versus 6.0782 for trend-only, a 9.8% improvement representing 112 months of independently collected data never seen during calibration. Residuals are normally distributed (Shapiro-Wilk p = 0.130), confirming well-conditioned model inputs. The full-sample retrained model (n = 84) estimates , forecasting January 2026 NTP at 123.91. This study constitutes the first BetaSutte application to a composite agricultural welfare index with two-year prospective out-of-sample validation.